Analysis of Factors Affecting Net Interest Margin in Foreign Banking Companies' Operations in Indonesia - Yoki Oktorian Sukardi; Evi Sofiati; Nurjamilah Nurjamilah (Center for Risk Management & Sustainability and RSF Press, 2026)
This research aims to empirically examine the factors influencing Net Interest Margin (NIM) in foreign banking companies operating in Indonesia. The study is grounded in the banking intermediation theory, which explains how banks manage financial resources to optimize profitability, and the risk-return tradeoff theory, which highlights the balance between risk factors and financial performance. Factors affecting NIM include the Loan to Deposit Ratio (LDR), efficiency ratio calculated by the ratio of operational expenses to operational income (BOPO), credit risk proxied by the Non-Performing Loan (NPL) ratio, and Market Share (MS). The research period covers the year 2019.A purposive sampling method was used, selecting 25 foreign banking companies that met specific criteria. Hypothesis testing was conducted using multiple linear regression analysis with EViews 10. Based on the results of panel data analysis, the t-test shows that the Market Share (MS) variable has a positive but insignificant effect on NIM. The Loan to Deposit Ratio (LDR) and Non-Performing Loan (NPL) variables have negative and statistically insignificant effects on NIM, whereas the Efficiency Ratio (BOPO) has a positive and statistically significant effect on NIM. The F-test results indicate that LDR, BOPO, NPL, and MS simultaneously affect NIM, with a significance value of 0.014544 (p < 0.05). The adjusted R² test results show that the predictive ability of these four independent variables is 33.68%, while the remaining 66.32% is influenced by other variables outside the model.